TRANSFORMING INTEREST IN IPAS LEARNING THROUGH THE INTERACTIVE MEDIA “EDUCAPLAY FROGGY JUMPS” - Dini Intan Fajriyah; Ansori (International Conference on Humanity Education and Society (ICHES), 2026)
The digital transformation in education since 2020 has encouraged the use of technology as an interactive and meaningful learning tool. However, based on observations at MI Nurur Rahman Tamanan Bondowoso, student learning interest in Natural and Social Sciences (IPAS) is still relatively low due to monotonous learning and the abstract nature of the material. Therefore, interactive media is needed to address this problem, one of which is the implementation of the interactive media Educaplay Froggy Jumps. This study aims to determine the application of Educaplay Froggy Jumps interactive media in the subject of science at MI Nurur Rahman Tamanan Bondowoso in the 2025-2026 academic year, and the effect of the use of Educaplay Froggy Jumps interactive media on students' interest in learning science at MI Nurur Rahman Tamanan Bondowoso in the 2025-2026 academic year. This research uses quantitative research with an experimental approach. Data collection techniques include: 1) observation, 2) questionnaires, and 3) documentation. The analysis uses descriptive and inferential analysis with simple linear regression tests assisted by SPSS Version 25. The results of the study showed that the use of Educaplay Froggy Jumps interactive media significantly increased students' interest in learning science, with different average values indicated by the mean of the experimental class of 63.04 while the control class was 56.81. The results of the hypothesis test showed a significance value of 0.000 <0.05 and t count of 6.488> t table of 1.708, so that the alternative hypothesis (Ha) was accepted with a coefficient of determination of 62.7% indicating that the increase in students' interest in learning was significantly influenced by the use of Educaplay Froggy Jumps interactive media.